Análise da contribuição da educação ambiental para a coleta seletiva de resíduos sólidos no ensino médio na cidade de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2008)
The study aimed at analyzing if there are programs of environmental education focusing on the selective collection of solid waste, developed in public and private high schools in the city of Manaus, able to accomplish a real behavioral change in students regarding their attitudes with environment as well as in the treatment of solid waste, reinforcing with the construction of proactive attitudes in the society, generating improvement in life quality and environment preservation. In the theoretical basis we present concepts and the importance in relation to environmental education according to a view of the socially and environmentally sustainable development to the success of modern economies for current and future societies benefit, characterizing the need of formation of environmental conscience in people and communities, rather than the importance of the school is present and its role as a motivational and transforming institution of the citizens behavioral change. Then studies were made related to solid waste, (concepts, problems, importance, causes and consequences) and the themes of environmental education to reduction and solution of these problems, besides their negative effects to economy and environment. After an analysis of collected data by means of questionnaires used and based on the theoretical basis approached, we concluded that the programs of Environmental Education developed in schools in Manaus do not demonstrate efficiency in accomplishing a behavioral change in people in regard to their behavior in defending the environment, specially about selective collection of waste, once they are not developed according to an inter, trans and multidisciplinary methodology, as well as the low yearly periodicity and the lack of continuity of actions and activities that involve the students programs and projects with the environment and the selective collection of solid waste.
Keywords: Educação ambiental; Coleta seletiva; Resíduos sólidos; Meio ambiente; Qualidade de vida.; Environmental education; Selective collection; Solid waste; Environment; Life quality; CIÊNCIAS SOCIAIS APLICADAS